Masculinities without men? : female masculinity in twentieth-century fictions - Noble, Jean Bobby (Vancouver : UBC Press, 2004)
"This groundbreaking study maps historical similarities in fictional, cultural, and representational practices between the periods of modernism and postmodernism. Noble examines nineteenth-century sexology, drama, and trial transcripts, and late twentieth-century counter-cultural fiction, popular film and documentaries, and theoretical texts. Among the works analyzed closely are texts that have been the focus of lesbian, queer, and feminist theory: Radclyffe Hall's The Well of Loneliness, Leslie Feinberg's Stone Butch Blues, and the film Boys Don't Cry. These, as Noble illustrates, make use of similar types of narratives, structures, and thematic techniques to articulate female masculinity. Also included is an exploration of Rose Tremain's Sacred Country, which has never before been studied within this context. Through a critical examination of these texts, Noble demonstrates that trans-gendered and trans-sexual masculinity began to emerge as a unique category in late twentieth-century fiction, distinct from lesbian or female masculinity."--Jacket.
Alibis of essence and enemies within : at the well of obscenity -- Passionate fictions : Radclyffe Hall's The well of loneliness -- Impressions of the man : sacred countries and the Stone butch blues -- Boys do cry : Hilary Swank and the politics of a pronoun -- Postscript : notes towards a radical (re)thinking of the politics of gender.
Includes bibliographical references (pages 168-176) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Gender identity in literature; Lesbianism in literature; Masculinity in literature; Fiction -- 20th century -- History and criticism; Women in motion pictures; Identité de genre dans la littérature.; Lesbianisme dans la littérature.; Masculinité dans la littérature.; Littérature -- 20e siècle -- Histoire et critique; Femmes au cinéma.; LITERARY CRITICISM -- Gay & Lesbian; Fiction; Gender identity in literature; Lesbianism in literature; Masculinity in literature; Women in motion pictures; Geschlechterrolle; Identität; Lesbische Orientierung; Literatur; Männlichkeit; Sekseverschillen; Mannelijkheid; Letterkunde; Lesbische liefde; 1900-1999; Electronic books; Criticism, interpretation, etc